La morphonologie du roumain : système d’alternances vs système de morphonèmes - Cychnerski, Tomasz (Studia Romanica Posnaniensia, 2020)
The paper confronts two models of the Romanian morphonological system. The first one is a complete set of alternations, which are based on three essential relations of purely formal opposition. These are 83 alternations that are even more subdivided, mainly by the criterion of their direction. The second one is made up of 117 morphonemes derived from directional alternations and is based on qualitative, quantitative and distributional opposition relations. Wider use can be achieved by a system of morphonemes, above all thanks to a strict way of defining the constituent units and their simple representation.